The Role of Social Support in the Relationship Between Job Insecurity and Turnover Intention Among Gen-Z Online Motorcycle Taxi Drivers in Pontianak City - Ritna Kurnia; Sunardi Ginting (Golden Ratio of Human Resource Management, 2026)
This study aims to analyze the role of social support as a moderating variable in the relationship between job insecurity and turnover intention among Generation Z online motorcycle taxi drivers in Pontianak City. This study employed a quantitative approach using a snowball sampling technique, involving 126 respondents. Data were collected through a Likert-scale questionnaire and analyzed using WarpPLS 0.7 software. The results indicate that job insecurity has a positive and significant effect on turnover intention (β = 0.43; p < 0.01), suggesting that higher levels of perceived job insecurity increase individuals’ intention to leave their current jobs. Interestingly, social support also has a positive and significant effect on turnover intention (β = 0.149; p = 0.043), indicating that, in this context, social support does not necessarily reduce employees’ intention to leave but may instead encourage them to pursue more stable employment alternatives. However, the moderating effect of social support on the relationship between job insecurity and turnover intention is not statistically significant (β = −0.084; p = 0.169). The R² value of 0.25 indicates that the variables examined explain 25% of the variance in turnover intention.